Perception of Patients on the Waiting List for Total Hip Arthroplasty on the Resumption of Elective Surgeries during the COVID-19 Pandemic - Pedrozo, Vitor Bernardes; Schuroff, Guilherme Zeni; Zaniolo, Francisco José; Deeke, Mark; Pedroni, Marco Antônio; Schuroff, Ademir Antônio (Revista Brasileira de Ortopedia, 2023)
Objective To analyze the profile and perception of patients on the waiting list for total hip arthroplasty (THA) about performing elective surgeries during the COVID-19 pandemic.Methods From July to November 2021, patients on the THA waiting list were interviewed during outpatient consultations. To compare the groups regarding categorical variables, the Chi-square test or Fisher's exact test was applied, and for quantitative variables the Mann-Whitney test was applied. The results were calculated using the Statistica program version 7.Results 39 patients answered the questionnaire. The mean age was 58.95 years, with 53.85% male. Approximately 60% expressed concern about contracting or transmitting COVID-19 to their family members after hospitalization for THA. 58.9% of patients felt hampered by the delay in scheduling elective surgeries during the pandemic. 23% lost or had a family member who lost their job during the pandemic, with a statistical difference for the group under 60 years old (p = 0.04).Conclusion Most patients were concerned about becoming infected and exposing family members to COVID-19 after surgery and noted damage due to suspensions and delay in scheduling elective surgeries. The economic impact of the pandemic was revealed by the rate of 23% of respondents who lost or had a family member who lost their job during the pandemic, being higher in patients under 60 years of age (p = 0.04).
Keywords: COVID-19; elective surgical procedures; arthroplasty, replacement, hip; patient perception of surgery